Institutional distrust trap: an analysis of the effect of public distrust in the Nigeria Police Force - Tiwa, Dany Franck A. (Policing and society, 2024)
This article explores an effect of distrust of the police – unwillingness to rely on them for security and justice – on policing dynamics in contemporary Nigeria using a qualitative research design. It argues that policing according to formal prescriptions such as the Criminal Procedure Act is virtually impossible in contemporary Nigeria because of this pervasive public distrust. At the same time, police officers resort to informal processes that further undermine public trust in the criminal justice system and create a self-defeating cycle that allows many to justify support for or active participation in illegal forms of crime control, including lynching by mobs and extra-legal killing by security forces. This proposition is significant for policing studies in two ways. Firstly, it suggests a trust threshold that, when breached, leads to policing collapse. Despite widespread distrust, many police forces maintain order. Secondly, it reveals how distrust perpetuates itself, even amid attempts at reform in various countries.